Quality of life of patients with neurofibromatosis 1—Physical disability does not necessarily result in poor mental health - Ute Bäzner; Leonie Stauss; Thomas Kapapa; Christian Rainer Wirtz; Christian Rainer Wirtz; Andrej Pala (Frontiers in Neurology, 2024)
IntroductionNeurofibromatosis 1 (NF1) is a chronic neurocutaneous disease known to profoundly affect quality of life (QoL). We have performed an analysis of disease severity, mental and physical QoL and compare the different subclasses among patients with neurofibromatosis 1 (NF1).Patients and methodsWe conducted a prospective analysis of 89 NF1 patients between January 2016 and March 2018. Data sourced from local records including demographic information, employment status, education level, and marital status. All patients completed 36-Item Short Form Health Survey (SF-36) and additionally the numerical pain rating scale (NPS). Patients were stratified based on severity of NF1, visibility and disease severity.ResultsAmong 89 patients, severity was classified as grade 4 was identified in 42 (47.2%), moderate in 17 (19.1%), mild in 23 (25.8%) and minimal in 7 (7.9%) cases. According to visibility scale, severe grade 3 was found in 28 (31.5%), moderate grade 2 in 26 (29.2%) and mild grade in 35 (39.3%) cases. SF-36 data, except for pain, showed significantly lower values, if compared to the standard German population (P < 0.001, physical component summary P = 0.045). Sex, marital status and education level did not significantly influence results. Employment was significantly associated with better mental and physical status (P = 0.028 and P = 0.01 respectively) and age >40 was linked to lower physical (P = 0.027) but not mental component scores (P = 0.362). The numerical pain rating scale indicated pain levels of 7–10 in 9 cases (10,1%), 5–6 in 10 patients (11.2%), 1–4 in 26 patients (29.2%) and no pain in 44 cases (49.4%). Physical component scores significantly differed across different NPS grades (P < 0.001) but not in mental component scores (P = 0.06). Finally, no significant differences were found in mental component scores across severity or visibility grades.ConclusionSeverity and visibility grades of patients with NF1 may not necessarily result in poor mental health. Symptomatic treatment should be considered even for severely disabled patients as they may have comparable QoL to less severely affected patients with NF1. Employment was linked to better quality of life outcomes in our findings.